The paradox of trust: How leadership, commitment, and inertia shape sustainability behavior in the workplace - Silvestre, W.; Begnini, S.; Abreu, I. (Administrative Sciences, 2025)
This study explores the factors driving employees’ sustainability-switching behaviors (SSBs) by integrating the Push, Pull, and Mooring (PPM) model with the Theory of Reasoned Action (TRA). A quantitative, cross-sectional survey was conducted with a convenience sample of 132 professionals actively involved in organizational sustainability initiatives across diverse industries and global regions. The findings reveal that leadership commitment significantly fosters both affective and normative employee commitments, with normative commitment positively influencing SSB. Surprisingly, organizational trust showed a negative impact on SSB, suggesting that employees may delegate responsibility for sustainability to the organization when trust is high. Inertia emerged as a strong barrier to behavioral change, independently inhibiting sustainability efforts. The study highlights the complex dynamics among leadership, trust, and inertia, offering practical insights for organizations aiming to foster sustainability. Addressing inertia directly and promoting shared responsibility for sustainability are critical for successful organizational transitions. Future research should explore the psychological mechanisms behind inertia and further investigate the paradoxical role of trust in sustainability initiatives.